Thermodynamic stabilities of NdFe3Al2, Nd5Fe17 and μ compounds and evolutions of microstructures and magnetic properties of Nd-Fe-Al alloys with nanocrystallites - Yanqin Cao; Changrong Li; Cuiping Guo; Zhenmin Du (Journal of Materials Research and Technology)
In the Nd-Fe-Al ternary system, thermodynamic stabilities of three compounds, NdFe3Al2, Nd5Fe17 and μ, were determined by the equilibrated alloys, indicating that both NdFe3Al2 and μ ternary compounds are metastable phases, while Nd5Fe17 compound is a stable phase. Meantime, the microstructures of five representative as-cast alloy buttons are illustrated, which are consisted of crystalline phases and the complex of nanocrystallites + amorphous matrix (NCAM). The crystalline phases including Nd, Nd3Al, Nd2Fe17-xAlx and Nd6Fe13-xAl1+x as well as the nanocrystallites such as dhcp-Nd, fcc-Nd and Nd6Fe13-xAl1+x embedded in the amorphous matrix were observed. Particularly, it is concluded that the fcc-Nd nanocrystallites may be transformed from the fcc dense packing clusters of the amorphous matrix and/or dhcp-Nd nanocrystallites. The hard magnetic properties of these as-cast alloys can be attributed to NCAM and present a non-strict proportionate effect. The alloy composed of Nd + NCAM, with curie temperature (Tc) 515 K, displays the highest intrinsic coercivity Hci 305 kA/m and remanent magnetization Br 10.8 emu/g. Its good glass-forming ability is presented by the high ratio (Tx/Tm) 0.88 and the small interval (Tm-Tx) 105 K of the crystallization temperature (Tx) with the melting temperature (Tm). Since the present investigation focuses on phase stabilities, microstructural characterizations, magnetic properties and glass-forming ability of the Nd-Fe-Al alloys, the obtained results can provide a better understanding for advancing the design of the Nd-Fe-Al based hard magnets and amorphous materials.